“Free Trade Area”: The Competitive Situation and Business Strategies in the Local Market of Blagoveshchensk - ЖуравскаяТатьяна Николаевна (Journal of Economic Sociology, 2010)
The Blagoveshchensk’s local market is characterized by a high level of competition, which is not typical for cities with such a low number of residents. One of the key factors is a town’s transboundary location (Blagoveshchensk is close to the Chinese border with the town Huai He across the Amur river) which entailed a formation of the so-called “free trade area”. It is characterized by a considerable number of new sellers entering the market, expectations of chain store companies’ invasion, reduction of the number of residents in the region, and relatively loose administrative control. The conducted research revealed a variety of business strategies in the food market and the market for household wares and consumer electronics including diversification and survival strategies. Many market sellers tended to copy successful trading formats due to fast information diffusion. And major trends observed in this distant region follow general trends developing in the central parts of Russia.